2010
DOI: 10.1371/journal.pcbi.1000860
|View full text |Cite
|
Sign up to set email alerts
|

Coding Efficiency of Fly Motion Processing Is Set by Firing Rate, Not Firing Precision

Abstract: To comprehend the principles underlying sensory information processing, it is important to understand how the nervous system deals with various sources of perturbation. Here, we analyze how the representation of motion information in the fly's nervous system changes with temperature and luminance. Although these two environmental variables have a considerable impact on the fly's nervous system, they do not impede the fly to behave suitably over a wide range of conditions. We recorded responses from a motion-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
(39 reference statements)
1
13
0
Order By: Relevance
“…Several invertebrate species were found to have firing-rate Q10 values above 2 (i.e., to double their neurons' firing rate), which is in line with the fact that many underlying biochemical processes also exhibit Q10 values of two or more (French and Kuster, 1982; Pfau et al, 1989; Warzecha et al, 1999; Hille, 2001; Spavieri et al, 2010). In contrast, we found that grasshopper auditory receptor neurons on average increased their firing rate by only ∼40–50% (corresponding to a Q10 value of 1.4–1.5).…”
Section: Introductionmentioning
confidence: 69%
“…Several invertebrate species were found to have firing-rate Q10 values above 2 (i.e., to double their neurons' firing rate), which is in line with the fact that many underlying biochemical processes also exhibit Q10 values of two or more (French and Kuster, 1982; Pfau et al, 1989; Warzecha et al, 1999; Hille, 2001; Spavieri et al, 2010). In contrast, we found that grasshopper auditory receptor neurons on average increased their firing rate by only ∼40–50% (corresponding to a Q10 value of 1.4–1.5).…”
Section: Introductionmentioning
confidence: 69%
“…To see whether we could infer the existence of such neural adaptation mechanisms, we compared the drop in photoreceptor response speed with the effects of falling light intensity on the motion-detecting neurons of other insects. In dipterans, the spiking rate of the motiondetecting neuron H1 does not change when light intensity falls from daylight levels to dusk levels (Egelhaaf et al, 2001) while the latency of the response increases by about 40 ms (more than twofold) with an intensity drop of three orders of magnitude from dim daylight levels (Spavieri et al, 2010). This study shows that in bumblebee photoreceptors, as light levels fall by over two orders of magnitude, the latency (described by the time-to-peak) increases by 24% and the response speed (described by corner frequency) decreases by 25% (see Table 2).…”
Section: Photoreceptor Voltage Response Modulationmentioning
confidence: 97%
“…The main findings point to timing changes with temperature decrease: period and burst interval decrease in acoustic [ 44 ] and electric [ 45 ] communication in fish. Acoustic perception seems to be deteriorated at lower temperatures in locust [ 46 , 47 ], as spiking variability increases with lower rates, the same effect that is present in the fly vision system [ 48 ]. Another widely studied model is the crab stomatogastric system, in which a central pattern generator, although increasing burst period and inner frequency, is able to compensate its phase over a wide range of temperatures [ 49 , 50 ].…”
Section: Introductionmentioning
confidence: 99%